IMMU-06. GCN2 KINASE IS ESSENTIAL FOR ADAPTIVE T-CELL IMMUNITY IN GLIOMA - Rashidi, Aida (Neuro Oncol, 2017)
GCN2 Kinase is a stress sensing enzyme that is activated upon amino acid depletion, shutting down global gene expression as a means of energy conservation. This gene has been implicated as the mechanistic explanation for how tryptophan depletion by indolamine 2-3-dioxygenase (IDO1) induces immunosuppression. The role that this pathway has in glioma immunosuppression is unknown. In this study we addressed T-cell responses in the absence of GCN2 in glioma bearing mice. Interestingly, after flow cytometric analysis of the brain infiltrating lymphocytes, there is a drastic decrease in the total T-cell infiltration in GCN2 knock out (KO) mice as compared to the wild-type mice, despite an increased survival benefit (p= 0.0066). In-vitro live/dead staining highlighted an increase in CD8 T-cell death, especially in the context of tryptophan depletion. Intracellular cytokine analysis revealed a significant decrease in T-cell activation and cytokine production by GCN2 deficient mice, arguing against T-cell mediated immunity influencing enhanced animal survival in these mice. Therefore, we analyzed the myeloid cells in the tumor bearing brain and we discovered that myeloid derived suppressor cells (MDSCs), in GCN2 KO mice had significant decrease in their expression of monocytic MDSCs (LY6C+), compared to the wild-type mice. To address the activity of the MDSCs, we co-cultured bone marrow derived MDSCs with OVA pulsed OT1 splenocytes, and our data demonstrate a significant decrease in the suppressive activity of the MDSCs from GCN2 KO as compared to wild-type mice, which potentially explains the increased survival of GCN2 KO mice with glioma. In conclusion, our data demonstrate that the GCN2 pathway is critical for CD8 T-cell function and fitness in the context of glioma, and must be taken into consideration as GCN2 inhibitors are currently in development for cancer therapy.